Memahami Efektivitas Komunikasi Pemasaran dalam Meningkatkan Penjualan Bisnis Cireng Isi - Okta Dilla Suryani; M. Taufiq Abadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Cireng isi, a popular Indonesian street food, is a lucrative business for street food vendors. To increase sales, vendors need to understand the effectiveness of marketing communication in promoting their products. One effective way is by utilizing social media platforms. Vendors can use e-commerce platforms such as Shopee and TikTok, as well as Instagram to expand their marketing reach. However, an effective marketing strategy needs to be tailored to the characteristics and behavior of each platform's users. In addition, product quality and customer service are also essential to maintain customer loyalty. This study used a qualitative approach to understand the experiences of cireng isi vendors in using social media for marketing. The results showed that social media can increase sales and expand the market reach but requires effective marketing efforts and strategies. Vendors must pay attention to product quality and customer service and understand the user characteristics of each platform to create an effective marketing strategy.